The innovation process in hospital services: a case study in an occupational therapy - Jacintho, José Carlos; Terra da Silva, Márcia; de Miranda Luzo, Maria Cândida (Brazilian Journal of Operations & Production Management, 2018)
The theoretical debates in the literature point to the need of innovations in hospital services. The objective of this article is to identify the conditions of services that facilitate or hinder the process for different types of innovation in hospital services. For this, case studies were developed that allow the identification of the types of innovation found in the physical rehabilitation outpatient clinics of the Occupational Therapy unit (OT) of the Orthopedics and Traumatology Institute (OTI) of the Clínicas’ Hospital of the Faculty of Medicine of the University of São Paulo (HCFMUSP). The data collected reveal that the results of hospital services are related to the process of developing innovations in the various stages of the workflow, from the generation of ideas to the diffusion within the hospital unit. On the other hand, the review of the literature based on the reverse cycle of Barras and the complements of Gallouj and Djellal show that the paths of innovation in hospital services and innovations in industrial organizations are opposite. Therefore, the results of the analysis of the five cases selected for study reveal that, under the integrative approach, a process change leads to a product change. Thus, the article concludes that, in hospital services, innovations are born within the organizational structure as well as in external contact with professionals, researchers and surgeons.